Investigation of athlete high school students' moral decision-making attitudes in terms of sport variables - Ozbek, Oguz; Nalbant, Umut (Gdansk Univ Physical Education & Sport, 2021)
Background: Sports activities are performed in accordance with moral values and principles. The purpose of this research is to examine the decision-making attitudes of young sports students based on age, gender, license status, and sports branch type. Material and methods: The Moral Decision-Making Scale in Youth Sports developed to evaluate the moral decision-making attitudes of young athletes was used as a data collection tool in this research. A five-point Likert scale was used to evaluate the scale items. Results: The athletes' views regarding moral decision-making attitudes were found to be for the Acceptance of Cheating dimension for the Acceptance of Gamesmanship dimension; and for the Keep Winning in Proportion dimension. It was determined that there was a significant difference in the student athletes' moral decision-making attitudes depending on gender, the type of sports played and being a certified athlete. Conclusions: Sports fields are the places where young athletes exhibit their skills and abilities in competitions. In these competitions, it should be emphasized to young athletes that respecting the values of the sport and following the rules is more important than winning and that they should stay away from negative behaviors such as cheating or gamesmanship.
Keywords: cheating; gamesmanship; moral decision-making; youth sports